Healing Under One Roof: Bridging Healthcare Needs in a Windsor, Ontario-Based Shelter Health Initiative - Zhou, Alex; Michael, Karen; Akintola, Temitope; Nguyen, Kim; Plantus, Rose; Guta, Adrian; Park, Grace; Pfaff, Kathryn; Voth, Jennifer; Foster, Jonathan; Shepard-Lemoine, Debbie; Sitarz, Hali; et al. (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Objective: People experiencing homelessness (PEH) face barriers to accessing healthcare, including competing demands that may outweigh or impede their access to healthcare, transportation barriers, and being lost to follow up. Current primary healthcare services are usually inadequate in meeting the needs of PEH due to inflexible appointments and fixed times with providers. The increasing incidence of homelessness in Windsor and the inability to meet their healthcare needs appropriately through current primary healthcare models are growing public health concerns. Windsor Shelter Health (WSH) is an integrated program offering on-site medical services at shelters and drop-in centers for PEH in Windsor, Ontario. A needs assessment survey was distributed to client-facing shelter staff to examine their perceived need for shelter health services and PEH’s most pressing healthcare needs. Methods: A survey was developed, validated, and distributed to client-facing staff across the WSH to understand how PEH access healthcare in Windsor and to identify any unmet healthcare service needs as understood by client-facing workers. This survey was distributed to client-facing workers through REDCap. Response frequencies and percentages were collected, stratified, and analyzed. Results: Survey results (n = 60) indicated strong support (96.7%) for establishing continuous, ongoing, and direct shelter health supports that are accessible to PEH. Services that were felt to be most important included access to primary care physicians, psychiatric care, addictions medicine, access to harm reduction, wound care assistance, and counselling. Delays in access to care were perceived to be due to clients’ fear and mistrust of the healthcare system, clients’ concerns regarding the stigma they experience, and poor access to transportation. Conclusion: Results of the survey will serve as a baseline for the development of targeted services to support and improve health care access and outcomes for PEH in Windsor. Establishment of shelter health services in the Windsor-Essex region will have strong public health implications, with long-term strategies requiring support from regional policies to address homelessness.